Respostas

2014-05-07T00:42:37-03:00
Y:4x+1
y = 4x+1
p/y = 0:
0 = 4x + 1
4x+1 = 0
x = -1/4

1 5 1
2014-05-07T00:54:13-03:00
Y=4x+1x.                                                                                                                                                  0=4x+1-4x=1-0=1/-4=1/4                                                                                                                      1=4x+1=-4x=1-1=x=0/-4=0                                                                                                                   2=4x+1=-4x=1-2=x=-1/4=1/4                                                                                                               3=4x+1=-4x=1-3=x=-2/-4=2/4                                                                                                              4=4x+1=-4x=-1=x=-3/4=3/4